Phytochemicals in cancer cell chemosensitization: Current knowledge and future perspectives. (May 2022) - Khatoon, Elina; Banik, Kishore; Harsha, Choudhary; Sailo, Bethsebie Lalduhsaki; Thakur, Krishan Kumar; Khwairakpam, Amrita Devi; Vikkurthi, Rajesh; Devi, Thengujam Babita; Gupta, Subash C.; Kunnumakkara, Ajaikumar B.
Abstract: Despite significant advancements made in the treatment of cancer during the past several decades, it remains one of the leading causes of death worldwide killing approximately 9.6 million people annually. The major challenge for therapeutic success is the development of chemoresistance in cancer cells against conventional chemotherapeutic agents via modulation of numerous survival and oncogenic signaling pathways. Therefore, sensitization of cancer cells to conventional drugs using multitargeted agents that suppress the survival and oncogenic pathways, in single or in combination, is an emerging strategy to overcome drug-resistance. During the last couple of decades, phytochemicals such as curcumin, resveratrol, tocotrienol and quercetin have emerged as potential chemosensitizing agents in cancer cells due to their less toxic and multitargeted properties. Numerous preclinical and clinical studies enumerated their potential to prevent drug resistance and sensitize cancer cells to chemotherapeutic agents by modulating several genes/proteins or pathways that regulate the key factors during the growth and progression of tumors such as inhibition of anti-apoptotic proteins, activation of pro-apoptotic proteins, reduced expression of different transcription factors, chemokines, enzymes, cell adhesion molecules, protein tyrosine kinases and cell cycle regulators. Therefore, natural chemosensitizing agents will have a special place in cancer treatment in the near future. This comprehensive review summarizes data obtained from various in vitro, in vivo and clinical studies to provide a new perspective for the application of agents obtained from "Mother Nature" as potential chemosensitizers for further cancer drug research and development.